Study an implementation of rack and pinion in the wash basin for hygienic hand washing. (2020) - Sathish, T.; Bala Subramanian, D.; Muthukumar, K.; Karthick, S.
Abstract: The water tank is fixed on the top of the equipment which is used to store the water. The pedal is connected to the shaft which is connected to the rack bar. When pedal moves down the moving shaft presses the rack bar to up side. When the rack bar goes upside also the pinion moves 90 Degree and it opens the tap, and allows flowing the water in the wash basin. When we left the pedal, the spring attachment mechanism compresses and again rack bar comes to the original position (i.e. down side). The tap is automatically closed. No wastage of water is occurred due to forget to close the tap. The project is used to operate the water pipe by leg through the easy operation of the pedal for washing purpose. It is very useful for physically challenged people and hand injured persons also. Our primary achievement is to avoid the contamination of the diseases. This project protect the people from the contamination and restricts the huge water wastage. The project is very useful for the hand injured persons. The project is used to operate the water pipe for hand washing purpose through the easy operation of pressing the pedal. This project is cheap in cost, and very useful for using on hotels, restaurant, public areas and home uses.